2011
DOI: 10.3109/03014460.2011.637512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and related metabolic traits in an island population of the Adriatic

Abstract: The Croatian islanders are characterized by a high prevalence of metabolic abnormalities. Central obesity is the strongest contributor of the syndrome. With a high prevalence of dyslipidemia and pro-inflammatory factors, the population is at substantial risk for cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Our study showed a higher prevalence of MetS in the continental region (due to diet), and in urban vs. rural residents (more physical activity). Similar results were shown by a study in Portugal, where a higher prevalence was found in older women in the continental region [30]. The prevalence of MetS, according to the NCEP definition, in the sample of 9 Dalmatian islands in 2006, was 34%, even reaching 47.2% on the island of Vis [17].…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed a higher prevalence of MetS in the continental region (due to diet), and in urban vs. rural residents (more physical activity). Similar results were shown by a study in Portugal, where a higher prevalence was found in older women in the continental region [30]. The prevalence of MetS, according to the NCEP definition, in the sample of 9 Dalmatian islands in 2006, was 34%, even reaching 47.2% on the island of Vis [17].…”
Section: Discussionsupporting
confidence: 85%
“…Of the publications found, only one publication was about the incidence of MVS [11], 50 articles were about the prevalence , 13 examined the co-ocurrence with type 2 diabetes (T2DM), and 29 the coexistence of the MVS with cardiovascular diseases (CVD) [14,19,20,23,24,29,30,33,34,38,39,42,43,45,57,63,64,[66][67][68][69][70][71][72][73][74][75][76][77]. There was no study about the natural history of the MVS.…”
Section: Selection Processmentioning
confidence: 99%
“…Our study population derives from a genetic epidemiology study in an isolated island population in the eastern Adriatic coast of Croatia, with obesity, hypertension, and MetS rates similar to US populations (15,16,30,31). Croatian islanders are predominantly of Slavic descent, having last emigrated to the Adriatic islands between the 15th and 18th centuries (32).…”
Section: Methodss Population and Phenotypic Measurementsmentioning
confidence: 99%
“…Over one-third of adult Americans meet the diagnostic criteria of metabolic syndrome [MetS; (1)], a clustering of metabolic disturbances that increase risk for type 2 diabetes, cardiovascular diseases, and even cancer (2)(3)(4)(5)(6)(7)(8). The worldwide prevalence of MetS is growing, most notably in developing nations where it follows obesity trends, sedentary lifestyles, and excessive caloric intake (9)(10)(11)(12)(13)(14)(15)(16). Although formal definitions of MetS from the World Health Organization (17), National Cholesterol Education Program Third Adult Treatment Panel III [NCEP ATPIII (18)], American Heart Association/National Heart, Lung and Blood Institute (19), and International Diabetes Federation (20) differ somewhat, the most relevant ele-ments of MetS diagnosis are well established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation